Attitude of resident doctors towards intensive care units′ alarm settings - Rakesh Garg; Anju R Bhalotra; Nitesh Goel; Amit Pruthi; Poonam Bhadoria; Raktima Anand (Indian Journal of Anaesthesia, 2010)
Intensive care unit (ICU) monitors have alarm options to intimate the staff of critical incidents but these alarms needs to be adjusted in every patient. With this objective in mind, this study was done among resident doctors, with the aim of assessing the existing attitude among resident doctors towards ICU alarm settings. This study was conducted among residents working at ICU of a multispeciality centre, with the help of a printed questionnaire. The study involved 80 residents. All residents were in full agreement on routine use of ECG, pulse oximeter, capnograph and NIBP monitoring. 86% residents realised the necessity of monitoring oxygen concentration, apnoea monitoring and expired minute ventilation monitoring. 87% PGs and 70% SRs routinely checked alarm limits for various parameters. 50% PGs and 46.6% SRs set these alarm limits. The initial response to an alarm among all the residents was to disable the alarm temporarily and try to look for a cause. 92% of PGs and 98% of SRs were aware of alarms priority and colour coding. 55% residents believed that the alarm occurred due to patient disturbance, 15% believed that alarm was due to technical problem with monitor/sensor and 30% thought it was truly related to patient′s clinical status. 82% residents set the alarms by themselves, 10% believed that alarms should be adjusted by nurse, 4% believed the technical staff should take responsibility of setting alarm limits and 4% believed that alarm levels should be pre-adjusted by the manufacturer. We conclude that although alarms are an important, indispensable, and lifesaving feature, they can be a nuisance and can compromise quality and safety of care by frequent false positive alarms. We should be familiar of the alarm modes, check and reset the alarm settings at regular interval or after a change in clinical status of the patient.